Cone beam computed tomography findings of a large Adenomatoid Odontogenic Tumour in the anterior mandible- A case report (Annals of Medical Research, 2021)
None
Keywords: Adenomatoid Odontogenic Tumour; Cone Beam Computed Tomography; Mandible.